MAKNA GERAK TARI TANGGAI DI KOTA PALEMBANG SUMATERA SELATAN - gabriella Saras Katungga; S Syahrial (Institut Seni Indonesia Surakarta, 2019)
Tanggai Dance is a welcome guest dance in the city of Palembang. Tanggai Dance is one of the dance that until now continues to exist and become a dance that must be known and studied by young people especially women. It is not recklessly to dance the Tanggai dance, but dancers should also know the contents of the dance, because there is a value to be conveyed to the people who appreciate the Tanggai dance. There are two focus problems that will be researched and formulated in the research question which is how the form of Tanggai dance and what is the meaning of the movement of Tanggai dance in the city of Palembang. This research uses qualitative research methods. The research aims to discuss the shape and meaning of the dance movements of Tanggai. The discussion of the form uses the concept of Suzzane K. Langer and Soedarsono about the form which means the structure of a relationship of various factors that are intertwined. Discussion of the meaning of motion using the concept expressed by Anya Peterson Roice about the three things of use is, mimetic, abstract, and metaphoric. The result of this research is Tanggai dance in Palembang city is a packaging dance form for welcome guests. Related to the meaning of the whole movement of Tanggai dance that has the meaning of surrender to the Lord Almighty.Keywords: dance form and motion meaning.